The views of farm animal veterinarians about their roles and responsibilities associated with on-farm end-of-life situations - Deelen, Ellen; Meijboom, Franck L. B.; Tobias, Tijs J.; Koster, Ferry; Hesselink, Jan-Willem; Rodenburg, T. Bas (Frontiers in Animal Science, 2022)
Farm animal veterinarians are often involved in on-farm end-of-life (EoL) decisions and questions concerning euthanasia. These EoL decisions can be challenging for the veterinarian, particularly if the interests of the animal and owner are conflicting. Moreover, the challenge is related to fundamental assumptions about roles and responsibilities veterinarians ascribe to themselves in EoL situations. Getting insight into what role and responsibilities veterinarians ascribe to themselves in EoL situations is important to understand the challenges veterinarians face and to explore ways to enable them to deal with such situations. Existing literature and professional guidelines partially help to clarify expectations and role perceptions by the veterinarian. Nonetheless, they are not conclusive in terms of the role conception and responsibilities of the veterinarian in the context of EoL situations. To better understand role perceptions and views on responsibilities by veterinarians, in-depth semi-structured interviews were conducted with Dutch farm animal veterinarians. Patterns and diversity of responses regarding the role and responsibility concepts were characterized. In terms of roles in EoL situations, analyses show that 1) veterinarians define a variety of roles, 2) two fundamental dimensions underlie these roles namely a) the extent to which a veterinarian gets involved and b) the question of whose interests are taken into consideration by a veterinarian, 3) the identified roles function next to each other both on an inter- and intrapersonal level and 4) veterinarians change between roles. In terms of responsibilities in EoL situations, analyses show that 1) veterinarians describe multiple responsibilities, 2) a combination of responsibilities is perceived by individual veterinarians, and 3) responsibilities relate predominantly to specific animal sectors. A better understanding of the role and responsibility perceptions of farm animal veterinarians is valuable as it facilitates to get grip on the challenges veterinarians face in EoL situations and creates a starting point for how veterinarians can be supported to deal with the related conflicts of interest. The gained insights could be of value in the training of future veterinarians and lifelong learning of veterinarians as a tool to reflect on, and discuss, one’s role and responsibility in EoL situations.